Characterization of Genetically Targeted Neuron Types in the Zebrafish Optic Tectum - Robles, Estuardo; Smith, Stephen J.; Baier, Herwig (Frontiers in Neural Circuits, 2011)
The optically transparent larval zebrafish is ideally suited for in vivo analyses of neural circuitry controlling visually guided behaviors. However, there is a lack of information regarding specific cell types in the major retinorecipient brain region of the fish, the optic tectum. Here we report the characterization of three previously unidentified tectal cell types that are specifically labeled by dlx5/6 enhancer elements. In vivo laser scanning microscopy in conjunction with ex vivo array tomography revealed that these neurons differ in their morphologies, synaptic connectivity, and neurotransmitter phenotypes. The first type is an excitatory bistratified periventricular interneuron (bsPVIN) that forms a dendritic arbor in the retinorecipient stratum fibrosum griseum et superficiale (SFGS) and an axonal arbor in the stratum griseum centrale (SGC). The second type, a GABAergic nonstratified periventricular interneuron (nsPVIN), extends a bushy arbor containing both dendrites and axons into the SGC and the deepest sublayers of the SFGS. The third type is a GABAergic periventricular projection neuron (PVPN) that extends a dendritic arbor into the SGC and a long axon to the torus semicircularis, medulla oblongata, and anterior hindbrain. Interestingly, the same axons form en passant synapses within the deepest neuropil layer of the tectum, the stratum album centrale. This approach revealed several novel aspects of tectal circuitry, including: (1) a glutamatergic mode of transmission from the superficial, retinorecipient neuropil layers to the deeper, output layers, (2) the presence of interneurons with mixed dendrite/axon arbors likely involved in local processing, and (3) a heretofore unknown GABAergic tectofugal projection to midbrain and hindbrain. These observations establish a framework for studying the morphological and functional differentiation of neural circuits in the zebrafish visual system.